2017
DOI: 10.18632/oncotarget.15254
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell autocrine CXCL12/CXCR4 stimulates invasion and metastasis of esophageal cancer

Abstract: Esophageal cancer is one of the most common malignant tumors of the digestive tract. The greatest obstacle to the curing of esophageal cancer is its propensity to spread and metastasize. Esophageal cancer stem cells are considered the source for recurrence and metastasis of the tumors. While clinical evidence suggested that continuous up-regulation of CXCL12/CXCR4 was significantly associated with poor prognosis in patients with esophageal cancer, but the role and mechanism of CXCL12/CXCR4 in the invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Chemokines and their receptors control cancer development through regulation of leukocyte infiltration, tumourrelated angiogenesis, tumour-specific host immune responses, and cancer cell proliferation and migration [31]. Although the molecular mechanisms underlying cancer metastasis remain to be fully elucidated, accumulating evidence points on a significant role of CXCL12/CXCR4 in the process [32][33][34][35], suggesting that the CXCL12/ CXCR4 axis may be a potential therapeutic target in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines and their receptors control cancer development through regulation of leukocyte infiltration, tumourrelated angiogenesis, tumour-specific host immune responses, and cancer cell proliferation and migration [31]. Although the molecular mechanisms underlying cancer metastasis remain to be fully elucidated, accumulating evidence points on a significant role of CXCL12/CXCR4 in the process [32][33][34][35], suggesting that the CXCL12/ CXCR4 axis may be a potential therapeutic target in BC.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that CXCR4/ CXCL12 participates in cancer development (6,8,(15)(16)(17)(18). CXCR4 is the only chemokine receptor expressed by the majority of cancer cells, and its ligand CXCL12 can be secreted by tumor cells and stromal cells, including tumor-associated fibroblasts (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lin CH et al (30) demonstrated that CXCL12, acting through CXCR4 and activating the Rac/ERK and JNK signaling pathways, could induce the expression of connective tissue growth factor, which is a profibrotic protein, in human lung fibroblasts, and potentiate their transdifferentiation into myofibroblasts. Wang X et al (16) demonstrated that the autocrine CXCL12/CXCR4 axis can mediate the metastatic property of esophageal cancer stem cells depending on ERK1/2 signaling pathway. Tian Y et al (31) indicated that CXCL12 induced the migration of oligodendrocyte precursor cells via the CXCR4 dependent MEK/ERK and PI3K/AKT pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12 also regulates the catabolic activity of chondrocytes by stimulating the release of matrix metalloproteinases and aggrecanases in vitro (Kanbe et al, 2002;Chinni et al, 2006;Lu et al, 2016). The CXCL12/CXCR4 axis plays a major role in the repair of cartilage by acting as a chemoattractant for inflammatory and stem cells (Brand et al, 2005;Hu et al, 2013;Wang et al, 2017). The CXCL12/CXCR4 axis may therefore play dual roles in early stage OA.…”
Section: Introductionmentioning
confidence: 99%